Ablation of TGFBR3 (betaglycan) in oocytes does not affect fertility in female mice. Issue 3 (March 2021) - Li, Yining; Lin, Yeu-Farn; Zhou, Xiang; Clarke, Hugh J; Bernard, Daniel J
Abstract : Ovarian follicle development is regulated by locally produced TGFβ superfamily members. The TGFβ type III receptor (TGFBR3, or betaglycan), which regulates the actions of diverse TGFβ ligands, including inhibins, is expressed in different ovarian cell types. However, its functional roles in the ovary have not been investigated in vivo . Here, we ablated Tgfbr3 in murine oocytes using the Cre-loxP system. Oocyte-specific Tgfbr3 knockout (cKO) females were fertile, producing litters of similar size and frequency as controls. Their ovarian weights and histology were also normal. Though we confirmed efficient recombination of the floxed alleles, we did not detect Tgfbr3 mRNA in purified oocytes from superovulated cKO or control mice. These results challenge earlier observations of betaglycan protein expression in this cell type. Regardless, Tgfbr3 in the murine oocyte is clearly dispensable for female fertility.